CCD-BASED SPECTROSCOPY OF WOLF-RAYET STARS: STUDY OF EXPANSION VELOCITY AND MASS LOSS AS A CONTRIBUTOR IN INTERSTELLAR MATTER ENRICHMENT - Adhyaqsa, Azlizan
Wolf-Rayet stars was discovered by C.Wolf and G.Rayet in 1867. In the spectra of Wolf-Rayet stars, broad emission lines caused by Doppler broadening can be observed. This indicate that Wolf-Rayet stars have high expansion velocity. It is also known that Wolf-Rayet stars have high mass loss rates compared with other type of stars. Thus, it is indicated that the expansion velocity and mass loss of WolfRayet stars have a role in interstellar enrichment. Based on the observed emission lines, Wolf-Rayet stars can be classi?ed as WN, WC, or WO stars. Optical spectroscopy was conducted on the night of July 5th and August 2nd 2018 using NEO-R1000 (R = ?? ? ? 1000) spectrograph attached on 10-inch Celestron C-11 telescope (F/10) with SBIG ST-8 XME CCD camera (1530 × 1020 pixels). From the observations, ?ve spectrograms of WN stars, three spectrograms of WC stars, and two spectrograms of spectrophotometric standard star were obtained. Then, the spectrograms were reduced using Image Reduction and Analysis Facility (IRAF). The data analysis was consisted of line identi?cations, determination of expansion velocities, and determination of mass loss rates. Line identi?cations were carried out based on multiplet tables by C. E. Moore (1945), expansion velocities were determined with Gaussian decomposition on the emission lines, and mass loss rates were determined with modelling using Potsdam Wolf-Rayet Models (PoWR). The obtained expansion velocities are within range of 1751?2641 km/s for WN stars and 1730?2516 km/s for WC stars. For the mass loss rates, the value are within range of 0.19×10?5?17.03×10?5 M/year for WN stars and 1.49×10?5? 2.09 × 10?5 M/year for WC stars. Assumed that the total of Wolf-Rayet stars in the Galaxy is ? 2600 (Kanarek, 2017), it is estimated that the Galactic WolfRayet population release ? 0.46 M every year. In the local scale, the expansion velocity of Wolf-Rayet stars play a role in creating structures of Wolf-Rayet nebulae. In some cases, interstellar enrichment by Wolf-Rayet stars can also be observed in Wolf-Rayet nebulae.